(untitled) (Homoeopathy for All, 2025)
A considerable percentage of women of reproductive age experience ovulation discomfort, also known as Mittelschmerz, during the mid-cycle period. It can be distressing and mimic severe abdominal problems, but it is usually benign and self-limiting. Reassurance and symptomatic treatment are the cornerstones of conventional management. A comprehensive therapeutic option, homeopathy treats both acute pain and underlying constitutional issues. The epidemiology, etiopathogenesis, diagnosis, and homeopathic treatments of Mittelschmerz are covered in this article, with a focus on customized care.